2001
DOI: 10.4049/jimmunol.167.3.1830
|View full text |Cite
|
Sign up to set email alerts
|

B7 Interactions with CD28 and CTLA-4 Control Tolerance or Induction of Mucosal Inflammation in Chronic Experimental Colitis

Abstract: CD28-B7 interaction plays a critical costimulatory role in inducing T cell activation, while CTLA-4-B7 interaction provides a negative signal that is essential in immune homeostasis. Transfer of CD45RBhighCD4+ T cells from syngeneic mice induces transmural colon inflammation in SCID recipients. This adoptive transfer model was used to investigate the contribution of B7-CD28/CTLA-4 interactions to the control of intestinal inflammation. CD45RBhighCD4+ cells from CD28−/− mice failed to induce mucosal inflammatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
67
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 53 publications
3
67
2
Order By: Relevance
“…In contrast, in vivo blocking with anti-CTLA-4 mAb did not have a similar effect on colitis induction (data not shown). The previous results from in vivo blocking with CTLA-4 mAbs have not been consistent, with one study finding increased weight loss after CTLA-4 Ab treatment (15) and another reporting no effect when pathogenic T cells were transferred in the absence of regulatory T cells (46). We found that blockade of CTLA-4 with mAb up-regulated IL-2 in our culture system during priming.…”
Section: Cd45rbcontrasting
confidence: 39%
See 2 more Smart Citations
“…In contrast, in vivo blocking with anti-CTLA-4 mAb did not have a similar effect on colitis induction (data not shown). The previous results from in vivo blocking with CTLA-4 mAbs have not been consistent, with one study finding increased weight loss after CTLA-4 Ab treatment (15) and another reporting no effect when pathogenic T cells were transferred in the absence of regulatory T cells (46). We found that blockade of CTLA-4 with mAb up-regulated IL-2 in our culture system during priming.…”
Section: Cd45rbcontrasting
confidence: 39%
“…The absence of adjuvant in colitis could render priming and subsequent CTLA-4 induction more sensitive to the absence of one B7 molecule. In one previous report (15), however, it was found that colitis caused by CD4 ϩ…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells are generated in the thymus and then exported to the periphery to maintain self tolerance (15,18,20). Naturally suppressive CD4 ϩ CD25 ϩ T cells have been described as having a low proliferative capacity in vitro and as expressing CTLA-4 and cell surface-bound TGF-␤ that are required to exert suppression by cell-cell contact (19,(21)(22)(23)(24). Moreover, CD4…”
mentioning
confidence: 99%
“…Peyer's patches DCs that synthesize IL-10 were shown to down-regulate Th1 cell mediated autoimmunity (Steinbrink et al 1997). Immature or peripheral DCs (iDCs), that had low expression of co-stimulatory molecules, secreted cytokine IL-10, remained in the periphery and were shown to induce Th2 lymphocyte mediated immunological tolerance (Rissoan et al 1999;Liu et al 2001;Li et al 2006). Further studies showed that a major function of peripheral iDCs was maintenance of self-tolerance (Wilson, El-Sukkari, and Villadangos 2004;Steinman and Pope 2002).…”
Section: Dendritic Cells Can Initiate Immunological Tolerancementioning
confidence: 99%